Practitioner Review: Therapist variability, patient‐reported therapeutic alliance, and clinical outcomes in adolescents undergoing mental health treatment – a systematic review and meta‐analysis. (6th July 2017) - Murphy, Regina; Hutton, Paul
Abstract : Background: Previous meta‐analyses have only found small correlations ( r  =   .10 to r  =   .19) between therapeutic alliance and clinical outcomes in samples of adolescents receiving psychological therapy. Although study‐level variables have been found to moderate this, little is known about the impact of therapist variability. The present meta‐analysis aimed to address this gap by using patient‐therapist ratio as a moderator variable. Methods: Contrary to previous reviews of adolescent alliance, individual effect sizes were extracted using a preregistered conceptual hierarchy. Controlling for treatment‐level confounds, a random effects meta‐analysis assessed the moderating effect of patient‐therapist ratio on the alliance‐outcome relationship in predefined single‐predictor and multipredictor meta‐regressions. Results: The alliance‐outcome relationship was found to be larger than previously thought ( k  = 28, N  = 2, 911, r  =   .29, 95% Confidence Interval 0.21, 0.37; p  <   .0001, I 2   =   80%). When study samples exceeding the adolescent 12–19 age range were removed, the correlation rose ( k  = 15, N  = 1, 797, r  =   .34, 95% Confidence Interval 0.23, 0.45; p  <   .0001, I 2   =   83%). In contrast to research with adults, patient‐therapist ratio did not moderate this relationship in either single‐predictor ( p  =   .26) or multi‐predictor ( p  =   .22) models. Conclusions: The alliance‐outcome relationship for adolescents was larger than previously thought, and comparable to estimates in adult samples. The failure of patient‐therapist ratio to moderate its strength, however, challenges the hypothesis that variability in therapist characteristics is an important determinant of the alliance‐outcome effect in this age group.